The Effect of Causal Learning Model Integrated With Character Values On The Ability To Master Physics Concepts And Positive Attitudes Of High School Students - Dunia Purnama; Joni Rokhmat; Syahrial A (International Journal of Contextual Science Education, 2025)
This study aims to analyze the effect of causal learning model integrated with character values on the ability to master physics concepts and positive attitudes of high school students. The background of the research is based on the low concept ability and positive attitude of students caused by the dominance of conventional learning methods and the lack of integration of character values in the learning process. This study used a quasi-experimental approach with a nonequivalent control group design. The research subjects were 11th grade students of SMA Negeri 4 Mataram in the 2024/2025 school year. The experimental class received treatment using an integrated causal model of character values, while the control class used direct learning. The research instrument consisted of a concept mastery description test and a positive attitude questionnaire for students. Data analysis was carried out by testing validity, reliability, normality, homogeneity, and Mann-Whitney test. The results showed that the application of the integrated causalytic model of character values significantly improved the ability to master physics concepts and positive attitudes of students compared to conventional learning. This model is effective in encouraging students to think causally and analytically, as well as internalizing character values such as responsibility, cooperation, and honesty. Thus, the causal learning model integrated with character values can be an innovative alternative in improving the quality of physics learning and shaping positive student character.